Analysis of fixed language in the subtitled documentary film "The Real Da Vinci Code" - Martins, Cláudia (2013)
This paper is based on the assumption that audiovisual translation performs a social and cultural function over its viewers, thus still justifying studies that focus on linguistic issues. This is particularly striking for the reading literacy in countries such as Portugal, which are traditionally subtitling countries, even if dubbing and voice-over are also occasionally used, particularly in the case of documentaries and children’s programmes. Reading habits may often be restricted to the reading of subtitles. This substitution emphasises the need for considerable care with subtitles in order to make them appear as fluent and natural – fulfilling norms of ‘idiomaticity’ – that would read like a source language text or domesticated, and not like a translation of a source text, not foreignised. From the analysis of a limited sample of fixed expressions and their translation in the subtitling of a documentary film called “The Real Da Vinci Code”, it was possible to gather data that indicate that these expressions are as common in general language as in specialised languages, namely within the audiovisual context and the informative genre, i.e. documentary films. Finally, it was possible to identify a logical relation between the visual, sound and linguistic elements of a documentary, since their interaction strengthens the semiotic value of the fixed expressions.